Assessment of patient falls using the world health organization’s international classification for patient safety: a five-year retrospective study - Ciftcioglu Yalcin, Gulcan (Journal of the Pakistan Medical Association, 2026)
Aim: To evaluate patient fall incidents using a standardised patient safety classification. Methods: The retrospective, descriptive study was conducted from June to November 2023 in the Mardin province of Turkiye, and comprised data from 10 hospitals related to fall incidents occurring between June 2018 and March 2023. The cases were evaluated in the light of the World Health Organisation’s International Patient Safety Classification. Data was analysed using IBM SPSS Statistics software (Version 25.0). Results: Of 140 patients with mean age 50.8. 71 of the patients who experienced a fall were aged <18 (50.8%). Fall incidents were associated with facility-related factors, patient-related factors, and nursing staff shortages. Among facility-related falls, slippery floors and the absence of raised bed railings were the leading factors with 60 cases (42.9%). Patient-related falls were highest among those that occurred in paediatric units, with 53 cases (37.9%). Falls attributed to nursing staff shortages accounted for 27 cases, which is 19.2% of all cases. 71 of the patients who experienced a fall were aged <18 (50.8%). Falls occurred predominantly in inpatient units with 112 cases (80.6%), and in 115 cases (82.4%), the incident was witnessed by a family member/companion or a member of the healthcare team. Almost all of the falls (n=131, 93.6%) resulted in no injury. Conclusion: Falls occurred due to the complex interplay involving the healthcare facility, patients, and nurses. Key Words: Patients, Patient safety, Nurses.